UPAYA KEPALA SEKOLAH DALAM PENINGKATAN KOMPETENSI PROFESIONAL GURU DI MI MUHAMMADIYAH GRIPIT - Nurlaeli Wulandari; Irega Gelly Gera; Dwi Purbaningrum (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2022)
The aim in this study is to find out how the principal’s efforts in improving professional competence of teacher at MI Muhammadiyah Gripit. The method of the research is field research and it is descriptive qualitative. The location of the research at MI Muhammadiyah Gripit, Banjarmangu. The data sources used include primary data, namely the results of interviews with principals, teacher councils, guardians of students and students itself. Secondary data were obtained from documentation, photos of activities, archives, profiles of schools, and school record. Data collection techniques were carried out by observation, interviews, and documentation. The validity of the data by using triangulation. Data analysis techniques were carried out by collecting data, reducing data, and presenting data. The results of this study indicate that MI Muhammadiyah Gripit has a competent principal with a board of teacher whose professional level is already good. The position of the teacher as an educator requires a professional ability that is able to support the achievement of educational goals. The problems that occur in connection with increasing the professional competence of teachers at MI Muhammadiyah Gripit relate to: the gap in the status of PNS and non-PNS teachers and the weak IT skills of teachers at first. Increasing teacher professionalism is an effort made by school principals and school principals play an important role in tackling these problems. With the professional improvement, it is hope that teachers will be able to improve their knowledge, skills and good attitudes. The principal’s efforts to improve the professional competence of teachers include: KKG activities, seminars, training outside and inside the school, regular meetings held with teachers to discuss teacher problems.